Reduced Prefrontal Gyrification in Carriers of the Dopamine D4 Receptor 7-Repeat Allele With Attention Deficit/Hyperactivity Disorder: A Preliminary Report - Palaniyappan, Lena; Batty, Martin J.; Liddle, Peter F.; Liddle, Elizabeth B.; Groom, Madeleine J.; Hollis, Chris; Scerif, Gaia (Frontiers in Psychiatry, 2019)
Objective: Structural and functional abnormalities have been noted in the prefrontal cortex of individuals with neurodevelopmental disorders such as Attention Deficit/Hyperactivity Disorder (ADHD). Cortical thickness and gyrification, both of which have been reported as abnormal in the prefrontal cortex in ADHD, are thought to be modulated by genetic influences during neural development. We aimed to investigate the effects of a polymorphism of the dopamine DRD4 gene (the 7-repeat ‘risk’ allele) on thickness and gyrification as distinct parameters of prefrontal cortical structure in children with ADHD. Method: We obtained structural images and genetic samples from 49 children aged 9-15 years (25 with ADHD and 24 matched controls) and calculated measures of cortical thickness and gyrification. Results: We observed a significant interaction between diagnosis and genotype on prefrontal gyrification, largely driven by reduced inferior frontal gyrification in patients who carried the DRD4 7R allele. Furthermore, inferior frontal gyrification - but not thickness - related to everyday executive functioning in 7-repeat allele carriers across groups. Conclusions: Prefrontal gyrification is reduced in children with ADHD who also carry the DRD4 7R allele and it relates to critical functional skills in the executive domain in carriers of the risk allele. More broadly, these effects highlight the importance of considering precise neurodevelopmental mechanisms through which risk alleles influence cortical neurogenesis and migration.